2018
DOI: 10.1007/s40430-018-1192-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on machining and surface characteristics of AA5083 for cryogenic applications by adopting trim cut in WEDM

Abstract: This paper presents the experimental investigation on wire electrical discharge machining (WEDM) of aluminum alloy 5083 (AA5083), an exotic material widely used for cryogenic applications. In this work, an attempt has been made primarily to examine the influence of number of trim cuts on WEDM for the following responses: cutting speed, surface roughness, corner error and dimensional shift. AA5083 is one of the predominant materials used in cryogenic applications. It is inevitable to comprise the inherent prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 24 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…This improved surface integrity in TC. Selvakumar et al [34] examined the influence of number of trim cuts on cutting speed, surface roughness, corner error and dimensional shift during WEDM of AA5083. The authors observed that rough cut followed by one optimal trim cut produced maximum cutting speed with excellent surface finish.…”
Section: State Of Artmentioning
confidence: 99%
“…This improved surface integrity in TC. Selvakumar et al [34] examined the influence of number of trim cuts on cutting speed, surface roughness, corner error and dimensional shift during WEDM of AA5083. The authors observed that rough cut followed by one optimal trim cut produced maximum cutting speed with excellent surface finish.…”
Section: State Of Artmentioning
confidence: 99%
“…At the same time, the use of new oil-based ecological dielectrics makes the process even more precise and safer for the environment [12, 13, 14, 15, 16]. However, EDM has low productivity and is applicable only for conductive materials [17, 18, 19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon was observed because at higher cutting speed the wire lag increases. This wire lag reduces the profile areas due to increases in the corner error in outer parts as observed by Selvakumar et al 30 There are variations in decrease observed in 1mm triangle from 31%-54% at 30 and for 5mm triangle it was from 77% to 100% at 0 , 15 . As the variations were very feeble it may have been caused due to wire vibration resulting from sparking.…”
Section: Effect Of D On Profile Areasmentioning
confidence: 73%
“…The β parameter majorly influences mostly on corner outer profile areas. 30 This has a very low effect on the inner profiles during machining as found in ANOVA. From the main effects plot, we can observe that there are small variations of increase and decrease in normal β, these variations were due to the errors while machining.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation